Hedging Government Oil Price Risk - Daniel, James (IMF Working Papers; Working Paper, 2001)
Many governments are heavily exposed to oil price risk, especially those dependent on revenue derived from oil production. For these governments, dealing with large price movements is difficult and costly. Traditional approaches, such as stabilization funds, are inherently flawed. Oil risk markets could be a solution. These markets have matured greatly in the last decade, and their range and depth could allow even substantial producers, and consumers, to hedge their oil price risk. Yet governments have held back from using these markets, mainly for fear of the political cost and lack of know how. This suggests that the IMF, together with other development agencies, should consider encouraging governments to explore the scope for hedging their oil price risk.